Elevated [CO2] Mitigates Drought Effects and Increases Leaf 5-O-Caffeoylquinic Acid and Caffeine Concentrations During the Early Growth of Coffea Arabica Plants - Catarino, Ingrid C. A.; Monteiro, Gustavo B.; Ferreira, Marcelo J. P.; Torres, Luce M. B.; Domingues, Douglas S.; Centeno, Danilo C.; Lobo, Ana Karla M.; Silva, Emerson A. (Frontiers in Sustainable Food Systems, 2021)
Increasing atmospheric [CO2] is thought to contribute to changes in precipitation patterns, increasing heatwaves and severe drought scenarios. However, how the combination of elevated [CO2] and progressive drought affect plant metabolism is poorly understood. Aiming to investigate the effects of this environmental condition on photosynthesis and specialized metabolites in leaves of Coffea arabica during the early growth, plants fertilized with ambient (a[CO2]-400 ppm) and elevated (e[CO2]-800 ppm) [CO2] were exposed to well-watered (WW) or water-deficit (WD) regimes for 40 days. Over the 40-day-water-withdrawal, soil moisture and leaf water potential decreased compared to WW-condition. Elevated [CO2] stimulates CO2 assimilation (A) and intrinsic water use efficiency (iWUE) even under WD. Drought condition slightly changed stomatal conductance, transpiration rate and maximum quantum efficiency of photosystem II (PSII) regardless of [CO2] compared to WW-plants. Total soluble amino acid concentration did not change significantly, while total phenolic compounds concentration decreased under e[CO2] regardless of water regimes. The combination of e[CO2]+WD increased the 5-O-caffeoylquinic acid (5-CQA) and caffeine amounts by 40-day when compared to a[CO2]+WD plants. Altogether, these results suggest that e[CO2] buffers mild-drought stress in young C. arabica by increasing A, iWUE and stimulating changes in the leaf contents of 5-CQA and caffeine.